2021
DOI: 10.1155/2021/2134082
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Mechanical Properties of a Novel Recycled Aggregate Concrete with Recycled Lightweight Aggregate

Abstract: A novel recycled aggregate concrete was prepared by replacing the natural aggregate with recycled lightweight aggregate. Subsequently, the mechanical properties and compressive stress-strain constitutive relation of the recycled lightweight aggregate concrete (RLWAC) were explored. For this purpose, the recycled lightweight aggregate (RLWA) replacement ratio (0%, 25%, 50%, 75%, and 100%) was selected as a variable, and the compressive strength of 15 cube and 30 prism specimens was evaluated. The failure morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…His study is mainly on the macroscopic properties of concrete and lacks the corroboration of microscopic properties. By studying the macroscopic mechanical properties of RAC with different replacement rates, Li et al [9] found that the higher the replacement rate of RCA, the worse the mechanical properties compared to ordinary concrete and constructed the stress-strain equation for reinforced concrete. Wang et al [10] studied the effect of RAC in complex environments mainly from a microscopic perspective.…”
Section: Introductionmentioning
confidence: 99%
“…His study is mainly on the macroscopic properties of concrete and lacks the corroboration of microscopic properties. By studying the macroscopic mechanical properties of RAC with different replacement rates, Li et al [9] found that the higher the replacement rate of RCA, the worse the mechanical properties compared to ordinary concrete and constructed the stress-strain equation for reinforced concrete. Wang et al [10] studied the effect of RAC in complex environments mainly from a microscopic perspective.…”
Section: Introductionmentioning
confidence: 99%